Prehabilitation Practices for Paediatric Haematopoietic Stem Cell Transplantation: A Survey and Patient and Public Involvement Study of Healthcare Professionals - Hala AbuSalameh; Raquel Revuelta Iniesta; Deborah Rowley (Nutrients, 2026)
Background/Objectives: Haematopoietic stem cell transplantation (HSCT) causes substantial morbidity in children and young people (CYP). Although prehabilitation benefits adults with cancer, its role in paediatric HSCT remains underexplored. This study aimed to describe current pre-transplant assessment and supportive care practices across paediatric HSCT centres, explore healthcare professional perspectives on prehabilitation implementation, and integrate patient and public involvement (PPI) to inform future intervention design. Methods: A cross-sectional survey was administered to healthcare professionals across 16 paediatric HSCT centres in the UK and the Republic of Ireland, alongside semi-structured PPI discussions conducted with eight children, young people, and caregivers with direct experience of paediatric HSCT. Survey data were analysed descriptively, free-text responses by qualitative content analysis, and PPI by reflexive thematic analysis. Results: Forty-nine eligible responses were received from healthcare professionals. Formal prehabilitation services were reported by 27 (55.1%) respondents, with substantial within-centre variation. Nutritional advice was the most consistently delivered component, 36 (72%), whilst physical activity interventions were the least consistently provided, 13 (26%). Workforce limitations were identified as the dominant barrier by 37 (95%) respondents. PPI findings described provision as reactive and inconsistent, with families expressing preference for flexible, hybrid, and family-centred delivery models. Conclusions: Prehabilitation provision in paediatric HSCT is variable, often informal, and limited by workforce capacity. CYP and caregivers expressed a desire for prehabilitation, particularly through flexible, hybrid (face-to-face and online), and family-centred approaches. Future research should prioritise co-design and feasibility testing of safe, individually tailored programmes that can be integrated into paediatric HSCT pathways.